Perceptions on support, challenges and needs among parents and caregivers of children with developmental disabilities in Croatia, North Macedonia and Serbia: a cross-sectional study - Međaković, Jelena; Čivljak, Antonia; Zorchec, Tatjana; Vučić, Vesna; Ristić-Medić, Danijela; Veselinović, Aleksandra; Čivljak, Marta; Puljak, Livia (Springer Science and Business Media LLC, 2024)
Parents/caregivers of children with developmental disabilities (CDD) have a wide range of support needs and there are various interventions available. Support, challenges, and needs among parents/caregivers of CDD likely vary in different geographical settings. This study aimed to analyze the perceptions of support, challenges, and needs among parents/caregivers of CDD in Croatia, North Macedonia, and Serbia.
Keywords: Caregivers; Children with developmental disabilities; Perception; Challenges and needs